EFEKTIVITAS MEDIA MIND MAPPING BERBASIS AUDIO UNTUK MENINGKATKAN PEMAHAMAN PERENCANAAN KARIER - Dinna Aprilia; Siti Fatimah; Muhammad Rezza Septian (IKIP Siliwangi, 2023)
Many junior high school students do not understand career planning, therefore students need to be given an understanding of career planning. This_study_aims_to_determine_the effectiveness of audio-based mind mapping media to improve understanding of career planning for class IX students of SMP Al-Mahmud Plus Cililin.”The subjects in this study amounted to 30 students of class IX and were selected based_on_the recommendations ofguidance_and_counseling_teachers on consideration by looking at the low level of understanding of career planning. This_study_uses_quantitative_research_with_experimental_methods, namely pre-experimental one group pretest-posttest design.”Data analysis used normality test and T test, the process of testing audio-based mind mapping media was carried out by distributing questionnaires and calculating effectiveness using SPSS. The results of normality show that the pretest significance value is 0.411 and the posttest is 0.326 so that in this normality test, the research data can be said to be normally distributed because it has a significance value of 0.05. The results of the t-test showed a 2-tailed significance value of 0.000 in this t-test there was a difference between the pretest and posttest variables. The results of the t-test carried out can be seen that the audio-based mind mapping media developed in this study is effective for career planning for class IX students of SMP Al-Mahmud Plus Cililin.”